Effect of Ozone and Two Common Denture Cleaners on Tensile Bond Strength and Surface Hardness of a Silicone Soft Liner - Mohammadreza Nakhaei; Amirtaher Mirmortazavi; Mansooreh Ghanbari; Zahra Ahmadi (Tehran University of Medical Sciences, 2020)
Objectives: To evaluate the effect of ozone and two common denture cleansers on the surface hardness and bond strength of a silicone-based soft liner to acrylic denture base material. Materials and Methods: Sixty cylindrical specimens were fabricated using heat-cured poly-methyl methacrylate denture base resin. Three millimeters of the material was ground from the midsection and filled with the soft liner. The resilient liner specimens (n=40) used for the hardness test were 10 mm in diameter and 5 mm in height. Cylindrical and disc-shaped samples were randomly divided into four groups (37°C distilled water, Corega® tablets, 0.5% sodium hypochlorite (NaOCl), and a home ozone generator). To simulate six months of denture cleansing clinically, samples were placed in their cleanser once a day for six months according to the manufacturer's instructions. All cylindrical specimens were placed under tension until failure in a universal testing machine at a crosshead speed of 5 mm/minute. For disc-shaped samples, hardness was measured using a Shore-A durometer. The results were analyzed using Kruskal-Wallis test, analysis of variance (ANOVA), and Tukey's post hoc test. Results: The mean tensile bond strength was not significantly different among the studied groups (P>0.05). The mean hardness in the ozone and Corega tablet groups was significantly lower than that of the control and NaOCl groups (P<0.05). Conclusion: The type of denture cleanser does not affect the tensile bond strength of silicone soft liners. Home ozone generators and cleansing tablets have less effect on the hardness of soft denture liners compared to 0.5% NaOCl.